Long-Term Treatment with Low-Level Arsenite Induces Aberrant Proliferation and Migration via Redox Rebalance in Human Urothelial Cells - Xiangli Yan; Qing Zhou; Shuhua Xi; Peiyu Jin (Cells)
Chronic exposure to arsenic via drinking water can induce bladder cancer in humans. Nevertheless, there is little knowledge about the precise mechanisms of this. Abnormal elevations in cell proliferation and migration have repeatedly been identified as the first cellular traits of carcinogenesis. The aims of this study are to uncover the molecular mechanisms underlying arsenic-induced aberrant proliferation and migration of uroepithelium cells by exploring the role of cellular redox modulation. Our results show significant elevations in the levels of ROS and GSH, Trx1, components of the Nrf2 system, and NLRP3 inflammasome activity in the cells chronically treated with arsenite, which also experienced markedly enhanced proliferation and migration capacities. Additionally, ROS inhibitors, NLRP3, and the above antioxidant system could suppress this enhancement of the proliferation and migration capacities and reverse overexpression in these cells. However, only the AKT and ERK inhibitors were capable of reversing EGF, TGFα, and HSP90 overexpression. In conclusion, our findings indicate that the cellular redox status in the uroepithelium following chronic treatment with low-level arsenite was rebalanced due to ROS overproduction and compensatory upregulation of the redox control systems, which may allow ROS and Trx1 to be maintained at higher levels to facilitate cell proliferation and migration via overstimulation of the related signaling pathways.